Brown Adipose Tissue Heterogeneity, Energy Metabolism, and Beyond - Shinde, Abhijit Babaji; Song, Anying; Wang, Qiong A. (Frontiers in Endocrinology, 2021)
Brown adipocyte in brown adipose tissue (BAT) specializes in expending energy through non-shivering thermogenesis, a process that produces heat either by uncoupling protein 1 (UCP1) dependent uncoupling of mitochondrial respiration or by UCP1 independent mechanisms. Apart from this, there is ample evidence suggesting that BAT has an endocrine function. Studies in rodents point towards its vital roles in glucose and lipid homeostasis, making it an important therapeutic target for treating metabolic disorders related to morbidities such as obesity and type 2 diabetes. The rediscovery of thermogenically active BAT depots in humans by several independent research groups in the last decade has revitalized interest in BAT as an even more promising therapeutic intervention. Over the last few years, there has been overwhelming interest in understanding brown adipocyte's developmental lineages and how brown adipocyte uniquely utilizes energy beyond UCP1 mediated uncoupling respiration. These new discoveries would be leveraged for designing novel therapeutic interventions for metabolic disorders.